IMPLEMENTASI METODE REST REQUEST PADA YOUTUBE WEB SERVICE UNTUK REPRESENTASI INFORMASI BERBASIS TIMELINE - Ryan Peterzon Hadjon; Restyandito Restyandito; Willy Sudiarto Rahardjo (Jurnal Informatika, 2015)
Developing video search application using the service of a third party data (resources) provider is a complex process. Therefore to obtain the desired data, an efficient communication method is needed. This research explored the use of REST request communication method by using URL to identify video resources through YouTube API data. Video data that were identified will then be processed to get more relevant video search. Relevancy of the search result was determined by applying the mechanism of relevance-based system and user-based system. Based on the experiment analysis, it is concluded that key word has an important role in determining the relevance of the search result, as it is needed for timeline based representation.